2020
DOI: 10.1007/jhep04(2020)091
|View full text |Cite
|
Sign up to set email alerts
|

Black hole entropy function for toric theories via Bethe Ansatz

Abstract: We evaluate the large-N behavior of the superconformal indices of toric quiver gauge theories, and use it to find the entropy functions of the dual electrically charged rotating AdS 5 black holes. To this end, we employ the recently proposed Bethe Ansatz method, and find a certain set of solutions to the Bethe Ansatz Equations of toric theories. This, in turn, allows us to compute the large-N behavior of the index for these theories, including the infinite families Y pq , X pq and L pqr of quiver gauge theorie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(124 citation statements)
references
References 75 publications
19
105
0
Order By: Relevance
“…Going beyond the Cardy-like limit, however, seems more formidable. The absence of a Bethe Ansatz description for the superconformal index seems to block a route that was successfully taken in the 4d context [42,43]. It would be interesting to consider near-BPS configurations by turning on temperature or slightly violating the BPS constraint (4.54), in the same spirit as [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Going beyond the Cardy-like limit, however, seems more formidable. The absence of a Bethe Ansatz description for the superconformal index seems to block a route that was successfully taken in the 4d context [42,43]. It would be interesting to consider near-BPS configurations by turning on temperature or slightly violating the BPS constraint (4.54), in the same spirit as [50].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have now independently reproduced the entropy function by studying the partition function or the superconformal index of N " 4 SYM [34][35][36] by slightly reinterpreting the original work in the superconformal index [26]. Further extensions for the general growth of the N " 1 superconformal index [37][38][39][40][41] including via the Bethe-Ansatz approach [42,43] have been achieved. After this important progress, the generalizations to other dimensions were also considered.…”
Section: Introductionmentioning
confidence: 99%
“…Using SLð2; ZÞ, the authors of Hong and Liu (2018) have found many other solutions of the Bethe equations for N ¼ 4 SYM at finite s. Non-standard solutions corresponding to continua of Bethe vacua have been found in Arabi . The solution (5.19) extends to more general quivers (Hosseini et al 2017c;González Lezcano and Pando Zayas 2020;Lanir et al 2020). 59 Notice that b is not really a temperature, but rather a parameterization of the modular parameter of the torus.…”
Section: 2mentioning
confidence: 92%
“…Following the insightful observation of [3], this puzzle has been revisited recently [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The emergent picture shows that there is actually an exponential growth of states contained in the index, which is captured by the saddle-point estimate if one allows the potentials σ, τ , ϕ to take values in the complex plane away from the pure imaginary values assumed in [2]. 1 There are essentially three strands of analysis contained in the recent progress:…”
Section: Jhep09(2020)184mentioning
confidence: 99%
“…The 20 This region lies inside the region in red in the figure 4 to the right which means that there is a supersymmetric (but not necessarily extremal) black-hole-like solution that exists in supergravity). 21 A partial phase diagram for N = 4 SYM was first presented in [8]. It focused on the subset of (1, r) configurations, with r ∈ Z which is equivalent to our figure 7 after mapping conventions (see Footnote 32).…”
Section: Cardy-like Limit(s) Revisitedmentioning
confidence: 99%